The effect of physical and psychological stress on the oral microbiome - Stoy, Savanna; McMillan, Alexandra; Ericsson, Aaron C.; Brooks, Amanda E. (Frontiers in Psychology, 2023)
Background: The oral microbiome is incredibly complex, containing a diverse complement of microbiota that is categorized into 6 broad phyla. While techniques such as next-generation sequencing have contributed to a better understanding of the composition of the oral microbiome, the role it plays in human health and disease is still under investigation. Previous studies have identified that a more diverse microbiome is advantageous for health. Therefore, alterations to the physical or mental health that are of interest in this study, such as stress, are the factors that decrease microbial diversity, leading to the potential for dysbiosis and disease disposition. Intensive Surgical Skills Week (ISSW) is a simulation training week for military medical students that takes place at the Strategic Operations (STOPS) facility in San Diego, CA. The training puts students through mass causality simulations and requires them to work through distinct roles within the healthcare team, providing an ideal environment to assess the impact of stress on oral microbiome diversity. Based on the literature on stress and microbiota, we hypothesized that the high stress simulation events at ISSW will impact the composition and diversity of the oral microbiome. Methods: Thirty-seven (n=37) second-or third-year medical students who are enlisted in a branch of the military and attended ISSW were included in the study. Student participants were divided into 7 teams to complete the hyperrealistic simulations (SIMs) at ISSW. A pilot of sixty-four buccal samples (n=64) from three of the seven teams were sent for analysis at the University of Missouri Metagenomic Center. Results: We saw an overall increase in species richness at the end of ISSW when looking at all samples (n=64). Fourteen significantly different bacteria were identified from the beginning to the end of data collection. Further, third year medical students appear to have a greater species richness compared to second year medical students. Conclusion: Our preliminary data indicates that physical and psychological stress can impact the composition of the oral microbiome. The analyses in this study show that using the oral microbiome as an indicator of stress is promising and may provide evidence to support stress management practices.